Students’ Perceptions of Artificial Intelligence Utilization in Islamic Education Learning at Junior High School - Indah Rahmawati; Mariana; Mutmainah; Yahya Mof; Muhamad Sabirin (Universitas KH. Abdul Chalim Pacet Mojokerto, 2026)
This study examines junior high school students’ perceptions of artificial intelligence (AI) utilization in Islamic Education (PAI) learning. Although AI use in education has increased, empirical studies focusing on students’ perceptions at the junior high school level, particularly in the context of Islamic Education, remain limited; this study addresses that gap. Using a descriptive quantitative approach, data were collected from 23 ninth-grade students through a 10-item Likert-scale questionnaire covering cognitive, affective, and conative aspects, with indicators including ease of use, content alignment with Islamic sources, satisfaction and trust, motivation and active learning, and ethics and responsible use. Likert-scale results were interpreted using predefined categorical intervals ranging from “very poor” to “very good.” The findings show an overall positive perception of AI utilization in PAI learning (mean = 4.07), categorized as “good.” The highest scores were found in ease of use and ethical use, while the lowest were related to content alignment with Islamic sources. These results indicate students’ positive attitudes toward AI accompanied by critical awareness of its limitations. The study highlights AI’s role as a supportive learning tool in PAI learning.